Online Expedition Services System for Customer at XYZ Ltd. - Nasa Zata Dina; Wilda Imama Sabilla; Irvandy Handoyo (LPPM Universitas Islam 45 Bekasi, 2020)
XYZ Ltd. is an expedition company that uses container ships and container trucks as transportation modes. There are three business process transactions that are carried out by the company, i.e. customer registration, ordering expedition services, and payment expedition services. Currently, all business process transactions are carried out manually, so process automation is needed in order for the business processes to run more effectively and efficiently. For this purpose, an Online Expedition Services Customer Service Information System was proposed to be built. This system consists of three main processes, namely the customer registration process, the customer order process, and the payment process and report generation. XYZ Ltd. Customer Service Information System was built following the waterfall development model. The stages of system development consist of five stages, namely planning, requirements analysis, database, and interface design, implementation of program code writing and testing and system maintenance. In implementing and testing the system, whole system requirements have been checked; the three main business processes in the proposed online system were running precisely, effectively and efficiently.